THE LIVESTOCK INDUSTRY OF MEXICO I LIVESTOCK STATISTICS - ALBA, JORGE DE (Rockefeller Foundation, CD MEXICO, DF, MEX, 1877)
Benzol exercises a specific central action on a zone of integration of panting and shivering; this zone may often be influenced by impulses mediated through the hypothalamus, as in the control of the body temp From the study of transections in acute expt
CATTLEMAN
Keywords: LIVESTOCK, INDUSTRY, MEXICO, LIVESTOCK, STATISTICS; CIENCIAS TECNOLOGICAS; TECNOLOGIA INDUSTRIAL; PROCESOS INDUSTRIALES